A candle in the dark: validity evidence for the Belief in Science Scale - Thiago Augusto Costa de Olival; Elaine Rabelo Neiva (Estudos de Psicologia (Campinas))
Abstract Objective The Science Belief Scale was developed with the aim of measuring the phenomenon in question, comprising 10 statements related to science and its associated worldview. This manuscript seeks to examine the psychometric properties of the instrument within the Brazilian context, with a particular emphasis on validity evidence. Method A translated and culturally adapted version of the instrument is presented, accompanied by an exploratory factor analysis (n = 662), as well as correlations between belief in science and personality traits, rationality, religion, sex, age, and educational attainment. Additionally, mean comparisons of science belief scores across religious groups were conducted. Results The findings indicate that the scale demonstrates robust internal and external validity, and given the assessed statistical power, the generalization of results appears justifiable with a reasonable degree of confidence. Conclusion The evidence of validity found in the study suggests that the satisfactory psychometric qualities of the scale for the Brazilian context may support new and broader investigations into individuals’ relationship with science as a belief.